How deep is your trust? A comparative user requirements’ analysis of automation in medical and mobility technologies - Sophia Hick; Hannah Biermann; Martina Ziefle (Humanities & Social Sciences Communications, 2024)
Abstract In a changing world full of innovative technologies, trust and trust requirements are increasingly important for designing user-centred systems and ensuring their long-term implementation. In this study, we explored and compared the requirements of future users to build trust in the two contexts of medical and mobility technology by considering Ambient Assisted Living technologies (AAL) and Shared Autonomous Vehicles (SAV). We conducted an online survey study with N = 143 participants. The results show significant differences in the evaluation of individual trust requirements in the two contexts about data sharing, data privacy and security as well as customization. Using a cluster analysis, we identified distinct user groups and trust personalities in both contexts (medicine and mobility). The clusters differ in terms of innovation openness and risk readiness, initial trust, and presence of chronic illness. Correlation analyses revealed significant relationships between people’s initial perceived trust in technology in the two contexts and their assessment of trust requirements, as well as their behavioural intentions to use SAV or AAL systems. Our findings indicate that trust requirements are context-specific and influenced by individual characteristics. This knowledge can be used to inform developers and distributors of technologies to design, build, and manage systems that meet the needs of future users.